The impact of corporate social responsibility (CSR) on firm’s financial performance. Evidence from selected rural banks in Ashanti Region - YAMOAH, KUSI OBED (KNUST, 2025)
A Thesis Submitted To The School Of Graduate StudiesIn Partial Fulfillment Of The Requirements For The Award Of Masters In Business Administration